Comparative Review of Aerobic and Anaerobic Composting for the Reduction of Organic Waste - Mckenzie, Imanni; Diana, Seecharran; Jaikishun, Sirpaul; Ansari, Abdullah (Agricultural reviews (Karnal, India), 2022)
Composting is a self-heating, aerobic, bio-decomposition process of organic waste that has advantages over other disposal strategies since it reduces waste volume by 40-50% and kills pathogens by the heat generated during the thermophilic phase. This process uses organic waste (food scraps, grass chipping, etc.), water, soil (for added microbes) and either incorporation of air by turning the compost (aerobic) or lack of air within the compost (anaerobic). This study is designed to comparatively assess aerobic and anaerobic composting mechanisms on the productivity rate and analyse the different variables influencing the process. Based on the results obtained the time taken to completely compost the organic materials might not always be the same, because composting time is dependent on the percentage of microorganisms, water content, temperature and C:N ratio present in the pile at the said time along with the amount of material to be composted. Finally, this study will not only help farmers but also the general public in choosing a cost-effective and environmentally friendly way of reducing organic waste from landfills and reduction of greenhouse gases in the ozone layer.